A computable general equilibrium analysis of policy options under the Nigeria’s National Economic Empowerment and Development strategy (NEEDS) -2 (2009)
The study uses a computable general equilibrium model of Nigeria to investigate the likely effects of two main policy options that will be given special consideration in the National Economic Empowerment and Development Strategy (NEEDS)-2 slated for implementation under the framework of the recently launched Seven-Point Agenda. The two policy options are the increase in the rate of value-added tax (VAT) and trade liberalisation. It is found. that an increase in VAT rate or a doubling of VAT rate for that matter will increase government revenue but this will be at the cost of a higher rate of inflation and impoverishment of poor households who are in the majority in Nigeria. This finding in part implies that the monetary authority concerned with price level stability should be on the alert whenever any attempt is made by the fiscal authority to increase VAT rate. Any attempt to liberalise trade (especially import) between Nigeria and other countries through the instrumentality of reduction in import duties' rates will boost both import and export transactions but this will at the same time reduce government revenue. One other interesting finding is that a higher percentage reduction in import duties' rates will result in a lower rate of naira depreciation and this sort of suggests that a higher percentage reduction in import duties' rates should be preferred to a lower percentage. The reduction in government revenue due to trade liberalisation implies that government will need to explore and exploit other sources of revenue to ensure sustainability of government expenditure.